2022
DOI: 10.3390/antiox11040751
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings on the Effect of Ultrasmall Superparamagnetic Iron Oxide Nanoparticles and Acute Stress on Selected Markers of Oxidative Stress in Normotensive and Hypertensive Rats

Abstract: Several studies have reported that the administration of various nanoparticles in vivo can cause oxidative stress. The combination of ultrasmall superparamagnetic iron oxide nanoparticles (USPIONs) and acute stress was selected because, during intravenous application of a contrast agent, patients are exposed to psycho-emotional stress. This study was designed to investigate the effect of acute stress and USPIONs on selected markers of oxidative stress (antioxidant capacity, superoxide dismutase, glutathione pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…NPs that have an inactive surface or low solubility can induce toxicity without causing oxidative stress [88]. In addition, in some works, it was shown that during the experimental therapy of animal models of pathology (stress, blood loss), magnetite NPs exerted an antioxidant effect [89,90].…”
Section: Targets and Mechanisms Of Toxic Action Of Magnetite Nanopart...mentioning
confidence: 99%
“…NPs that have an inactive surface or low solubility can induce toxicity without causing oxidative stress [88]. In addition, in some works, it was shown that during the experimental therapy of animal models of pathology (stress, blood loss), magnetite NPs exerted an antioxidant effect [89,90].…”
Section: Targets and Mechanisms Of Toxic Action Of Magnetite Nanopart...mentioning
confidence: 99%